2023
DOI: 10.3390/biology12040594
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Droplets from Plants and Microalgae: Characteristics, Extractions, and Applications

Abstract: Plant and algal LDs are gaining popularity as a promising non-chemical technology for the production of lipids and oils. In general, these organelles are composed of a neutral lipid core surrounded by a phospholipid monolayer and various surface-associated proteins. Many studies have shown that LDs are involved in numerous biological processes such as lipid trafficking and signaling, membrane remodeling, and intercellular organelle communications. To fully exploit the potential of LDs for scientific research a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 170 publications
0
3
0
Order By: Relevance
“…Synthesized TAG is stored in lipid droplets (LDs). LDs are enveloped by a phospholipid monolayer with embedded lipid droplet proteins, which are deposited on the LD membrane [48]. Mass spectrometry analysis showed that the major lipid droplet protein (MLDP) was a major protein in lipid droplets, and the inhibition of the expression of the MLDP-encoding gene, using RNAi, led to an increase in lipid droplet size, but no changes in triacylglycerol content or metabolism were observed [49].…”
Section: Triacylglycerol (Tag) Storagementioning
confidence: 99%
“…Synthesized TAG is stored in lipid droplets (LDs). LDs are enveloped by a phospholipid monolayer with embedded lipid droplet proteins, which are deposited on the LD membrane [48]. Mass spectrometry analysis showed that the major lipid droplet protein (MLDP) was a major protein in lipid droplets, and the inhibition of the expression of the MLDP-encoding gene, using RNAi, led to an increase in lipid droplet size, but no changes in triacylglycerol content or metabolism were observed [49].…”
Section: Triacylglycerol (Tag) Storagementioning
confidence: 99%
“…The schematic overview of the principal enzymes linked to enhanced triacylglycerol synthesis under stress conditions in the lipid synthetic pathways is provided in Figure 4. [235]. It depicts the synthesis of free fatty acids (FFAs) and triacylglycerols (TAGs) in both the endoplasmic reticulum and chloroplast.…”
Section: Abiotic Stress Induced Genes Responsible For Lipid Productionmentioning
confidence: 99%
“…TAGs are the primary storage lipids in algae, while sterol esters play a minor role. The lipid composition of membranes is more complex and heterogeneous, and it varies between different cell compartments, cell types, and even different organisms [235]. Cellular membranes are essential for maintaining cell integrity and functionality.…”
Section: Cell Membrane Lipid and Triglycerides Accumulated In Lipid D...mentioning
confidence: 99%